Hysteria! Season one [videorecording (DVD)]. - Campbell, Bruce, 1958-; Bowen, Julie; Camp, Anna, 1982-; Anthony, Emjay, 2003- (Universal Studios, 2025)
When a beloved varsity quarterback disappears during the "Satanic Panic" of the late 1980s, a struggling high school rock band of outcasts realizes they can capitalize on the town's sudden interest in the occult by building a reputation as a Satanic metal band, until a bizarre series of murders, kidnappings and reported "supernatural activity" triggers a leather-studded witch hunt that leads directly back to them.